Effects of cultivars and fertilization levels on the quality of brown and polished rice. Issue 6 (19th August 2021) - Coradi, Paulo Carteri; Müller, Amanda; André, Geovane da Silva; Teodoro, Paulo Eduardo; Campos, Cid Naudi Silva; Anschau, Kellen Francine; Flores, Erico Marlon Moraes
Abstract: Background and objectives: Adapting production factors and relating them to the effects of rice milling can contribute to obtaining better quality grains in the industry. Thus, the study had an objective to evaluate the effects of cultivars and fertilization levels in the physical, physicochemical, and morphological quality of the polished and brown rice. Findings: The starch underwent minor changes in its structure with increased fertilization levels, conserving the physicochemical rice composition for cultivar IR 431 Cl in the polished rice. However, the combination of cultivar IR 424 Cl and brown rice demonstrated positive correlations in crude protein and starch. In addition, positive correlations between the physical variables were obtained in full milling. Furthermore, brown rice had the highest percentages of whole rice in the high fertilization levels, whereas the polished grain contained the highest percentage of broken and yellow grains in the low fertilization levels. Conclusions: The rice cultivar IR 431 Cl produced with high fertilization levels had high protein and starch quality in the polished grains, while the cultivar IR 424 Cl produced high quality in brown rice. We conclude that the association of cultivars and fertilization levels in rice production obtained high rice quality according to milling type. Significance and novelty: It is possible to define the best way of milling rice in the industry to enhance the final quality, depending on the production factors adopted in the crop, such as the type of cultivar and fertilization levels.